Implementation Of The Ta'shil Method In Understanding The Ta'lim Al Mutaallim Book At The Tahfidzul Quran Al Iman Islamic Boarding School - Muhammad Askarullah Tsabit; Asrori Asrori; Rusman Rusman (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This study discusses the Ta'shil Method in understanding the Ta'lim Al Mutaallim Book, including: (1) Implementation of the Ta'shil Method in understanding the Ta'lim Al Mutaallim Book on Aqidah Akhlak material. (2) Strengths and weaknesses of the Ta'shil Method in understanding the Book of Ta'lim Al Mutaallim on Aqidah Akhlak material. The design used in this study is field research because the researchers went directly to the field to get data that were in accordance with the facts and made observations to collect data related to research on the implementation of the Ta'shil Method at Islamic boarding school al Iman Sedayulawas Lamongan in understanding the book Ta'lim al Mutaallim on Akidah Akhlak material, the results of this study are descriptive data obtained from interviewees as well as data that has been written and from the observations of researchers. The research was carried out at the Tahfidzul Qur'an Al-Iman Islamic Boarding School located in Sedayulawas village, Brondong district, Lamongan district, East Java province, this Islamic boarding school was founded in 2016 and was taken care of by Ustad Sofi Muallim. The results showed that: (1) Implementation of the Ta'shil method in understanding the Book of Ta'lim Al Mutaallim on the Aqidah Akhlak material at the Tahfidzul Quran al Iman Al Iman Al Iman Sedayulawas Lamongan First, Tadarruj (gradual), Second, Tikrar (Repeating), Third, Focus, Fourth, good mentoring. (2) The supporting factor for the ta'shil method at the Al Iman Islamic boarding school is that it is easy for students to build a stronger and more perfect understanding framework because it starts from the basics and always continues between books. The inhibiting factor for the implementation of the first ta'shil, the use of the ta'shil method, a cleric must attend class every day, if the ustad is unable to find a temporary substitute and this is not easy because he has to find a cleric who masters the book. The ta'shil method is a relatively new method in the Islamic boarding school environment, this makes people not sure about the results of this method.